2020
DOI: 10.1029/2019jd031618
|View full text |Cite
|
Sign up to set email alerts
|

River Regulation Alleviates the Impacts of Climate Change on U.S. Thermoelectricity Production

Abstract: Climate change is projected to elevate stream temperature and poses threats to thermoelectric power generation. Although two thirds of the global rivers are regulated by dams, the impacts of river regulation on stream temperature and thermoelectricity production have not been evaluated in previous studies. Using a state‐of‐the‐art integrated water cycle model and a power generation model, we quantify the impacts of river regulation on stream temperature and usable capacity of once‐through thermoelectric power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Stream water temperatures can be affected by several factors that include climate (e.g., air temperature, solar radiation, and wind velocity), hydrological processes (e.g., advection from upstream reaches, snowmelt and runoff, groundwater exchange), land cover (e.g., riparian shading), and human activities (e.g., discharge from thermal power plants, dam releases, diversions) [19][20][21][22]. Thus modeling water temperatures, particularly for decision-relevant spatial and temporal scales using purely process-based models based on physical equations can be complex and scale-dependent, and more importantly lack adequate representation of human influences.…”
Section: Introductionmentioning
confidence: 99%
“…Stream water temperatures can be affected by several factors that include climate (e.g., air temperature, solar radiation, and wind velocity), hydrological processes (e.g., advection from upstream reaches, snowmelt and runoff, groundwater exchange), land cover (e.g., riparian shading), and human activities (e.g., discharge from thermal power plants, dam releases, diversions) [19][20][21][22]. Thus modeling water temperatures, particularly for decision-relevant spatial and temporal scales using purely process-based models based on physical equations can be complex and scale-dependent, and more importantly lack adequate representation of human influences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generally shown that projected increases in stream temperature under climate change will put great pressure on potential electricity generation globally (van Vliet et al, 2012, van Vliet et al, 2013, van Vliet et al, 2016) and over regions of the United States (Bartos & Chester, 2015; Boehlert et al, 2015; Liu et al, 2017; Miara et al, 2017; Zhang et al, 2020) by reducing the cooling efficiency of thermoelectric plants. Power plants face capacity derating and resulting power outages if their thermal effluent temperature exceeds specific environmental thresholds (McCall et al, 2016; Raptis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of large‐scale stream temperature studies (Boehlert et al, 2015; Isaak et al, 2012; Li et al, 2015; Mantua et al, 2010; Strzepek et al, 2015; Sun et al, 2015; van Vliet et al, 2012; Zhang et al, 2020) accounted for the effects of reservoir regulation, most of them did not explicitly consider seasonal thermal stratification and therefore underestimated the effects of regulation on stream temperature, particularly downstream of large reservoirs. For example, Li et al (2015) showed a warm bias of over 10°C in summer stream temperature downstream of Hoover Dam and Yearsley et al (2019) showed a warm bias of as much as 8°C downstream of a reservoir in the Connecticut river basin.…”
Section: Introductionmentioning
confidence: 99%
“…E3SM v1 features a new river transport model, MOSART, which was designed as a framework for modeling riverine water, heat, and biogeochemical fluxes across scales (Li et al, 2013; Li, Leung, Tesfa, et al, 2015). Building on this framework, Li, Leung, Tesfa, et al (2015) described a new stream temperature module in MOSART, which provides an important capability for relating water availability to thermoelectric power generation (Zhang et al, 2020). MOSART also serves as a conduit for representing irrigation and water management.…”
Section: Highlights Of Modeling Challenges and Simulation Resultsmentioning
confidence: 99%